The State’s Obligation to Protect the Individuals Lives from the Consequences of Domestic Violence - Vilard Bytyqi (Faculty of Law, Hasanuddin University, 2017)
The aim of this paper is to treat the important aspects, which deal with State’s obligations to protect individuals lives from the consequences of the domestic violence. Thus, domestic violence is a concerning issue, which derives many consequences that sometimes are irreparable. In many cases, the State is obliged to save individuals lives from the effects of the domestic violence. The State will not be held responsible in all the cases for the consequences of the domestic violence. Due to the scarcity of the regulation of all the situations in the normative terms, the judicial practice that considers the cases of the right to live has evolved greatly, such that it has set many standards in case of increased institutional responsibility towards the consequences caused by the domestic violence. Due to a practical elaboration, the paper as a such will focus in the treatment of cases from the judicial practice in the context of the State’s obligation to save individual’s life, whose life is endangered. Furthermore, there will also be an emphasis in the protection of the right to life and the State’s responsibility in relation to the consequences caused by the actions of the third parties.